2015
DOI: 10.1007/s00240-015-0822-0
|View full text |Cite|
|
Sign up to set email alerts
|

In vitro inhibition of calcium oxalate crystallization and crystal adherence to renal tubular epithelial cells by Terminalia arjuna

Abstract: Urolithiasis is a multifactorial disease and remains a public health problem around the world. Of all types of renal stones, calcium oxalate (CaOx) is the most common composition formed in the urinary system of the patients with urolithiasis. The present study is aimed at evaluating the antiurolithiatic properties of the Tris-Cl extract (TE) of Terminalia arjuna (T. arjuna). The antilithiatic activity of TE of T. arjuna was investigated on nucleation, aggregation, and growth of the CaOx crystals, as well as it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 39 publications
1
27
0
Order By: Relevance
“…2 Development of plant-based medicine as alternative or complementary to the conventional system of medicine have drawn tremendous attention and serves as an immense source of new drug entities. 3 Based on these grounds, carrots (Daucus carota L., family Apiaceae) were selected for the present study. Carrots are considered functional food and are widely cultivated all around the globe as well as are extensively exploited commercially.…”
Section: Introductionmentioning
confidence: 99%
“…2 Development of plant-based medicine as alternative or complementary to the conventional system of medicine have drawn tremendous attention and serves as an immense source of new drug entities. 3 Based on these grounds, carrots (Daucus carota L., family Apiaceae) were selected for the present study. Carrots are considered functional food and are widely cultivated all around the globe as well as are extensively exploited commercially.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms involved in the formation of calcific stones are not fully understood. 5 Renal stone formation is a biological process that involves physicochemical changes and supersaturation of urine. 9 It is explained through of the loss of the equilibrium between promoters and inhibitors of the crystallization, 2 urine composition and renal morphoanatomy.…”
Section: Formation Of Renal Stonesmentioning
confidence: 99%
“…3,17 Recent studies have demonstrated that oxalate produce damage to renal cell by the generation of reactive oxygen species 18 ; which increase the surface expression of phosphatidylserine, sialic acid, hyaluronan, osteopontin, or the glycoprotein receptor CD44, resulting in more crystal adhesion and formation of the nidus for the formation of stone. 5 On the other hand, the presence of renal cavities with low urodynamic efficacy retain urine by long periods of time in the upper urinary tract, which favors the formation of stone. 19 Finally, there are substances in the urine act as inhibitors of lithogenesis through of the inhibition in the crystal surface; also, there substances have complexing properties with some ions involved in the precipitation process decreasing its concentration.…”
Section: Formation Of Renal Stonesmentioning
confidence: 99%
See 2 more Smart Citations